CARBAMAZEPINE AS A PAIN TREATMENT OF TRIGEMINAL NEURALGIA - Hanik Hidayati (Journal of Pain, Headache and Vertigo, 2020)
Pain and fear of pain continue to be the commonest and strongest motivation for the patients to seek medical help. Pain is a personal experience of the sufferer that cannot be shared and wholly belongs to the sufferer. Trigeminal neuralgia (NT) is a notable facial pain disorder resulting in periodic severe pain that produces one of the most severe kinds of pain known to mankind. Treatment of this debilitating condition may be varied, ranging from medical to surgical interventions. Anticonvulsant are commonly used for its treatment. One of anticonvulsant drug is carbamazepine (CBZ). This paper will discuss about the efficacy and tolerability of CBZ for the treatment of NT.